1997
DOI: 10.1046/j.1365-2036.1997.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ulcerative colitis with an engineered human anti‐TNFα antibody CDP571

Abstract: Background:Tumour Necrosis Factor‐alpha (TNFα) is a pro‐inflammatory cytokine whose expression is increased in the colonic mucosa of patients with active ulcerative colitis. TNFα antibodies have been shown to be beneficial in animal models of bowel inflammation and in Crohn's disease but have not previously been studied in ulcerative colitis.Methods:Patients with mild/moderate ulcerative colitis were treated openly with a single intravenous infusion of 5 mg/kg of an engineered human IgGγ4 antibody CDP571 and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
9

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(69 citation statements)
references
References 10 publications
2
58
0
9
Order By: Relevance
“…In our studies, we observed a dose-dependent fluid accumulation following direct injection of mice with TNF. Clinically, blocking TNF with mAb's (Infliximab) has been known to prevent diarrhea symptoms in patients with IBD (2,33). Similarly, we found that in mice, blocking TNF prior to T cell activation prevented fluid accumulation almost completely.…”
Section: Discussionsupporting
confidence: 57%
“…In our studies, we observed a dose-dependent fluid accumulation following direct injection of mice with TNF. Clinically, blocking TNF with mAb's (Infliximab) has been known to prevent diarrhea symptoms in patients with IBD (2,33). Similarly, we found that in mice, blocking TNF prior to T cell activation prevented fluid accumulation almost completely.…”
Section: Discussionsupporting
confidence: 57%
“…La segunda línea de evidencia proviene del tratamiento de animales de experimentación con CU idiopática con anticuerpos anti-TNF (CDP571). Dicho tratamiento conduce a aumento de peso y una mejoría histológica de la inflamación mucosa (21).…”
Section: Discussionunclassified
“…A second line of evidence is supplied by the experimental treatment of animals with idiopathic UC using anti-TNF-α antibodies (CDP571). Such treatment is followed by weight gain and a partial reversal of histological mucosal changes (21).…”
Section: Discussionmentioning
confidence: 99%
“…CDP571, an immunoglobulin G4 humanized monoclonal anti-TNF-antibody showed a slight and short lived reduction in clinical activity of UC [234]. It proved to be less effective than infliximab and further clinical development of CDP571 for the treatment of CD has been discontinued (see review [194]).…”
Section: Inhibition Of Pro-inflammatory Cytokines 3211 Inhibitorsmentioning
confidence: 99%